2021
DOI: 10.1038/s41746-021-00469-6
|View full text |Cite
|
Sign up to set email alerts
|

Yet Another Automated Gleason Grading System (YAAGGS) by weakly supervised deep learning

Abstract: The Gleason score contributes significantly in predicting prostate cancer outcomes and selecting the appropriate treatment option, which is affected by well-known inter-observer variations. We present a novel deep learning-based automated Gleason grading system that does not require extensive region-level manual annotations by experts and/or complex algorithms for the automatic generation of region-level annotations. A total of 6664 and 936 prostate needle biopsy single-core slides (689 and 99 cases) from two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…The model and designated pathologist had an AUC of 0.960 for identifying cancer and a mean pairwise kappa of 0.62 for assigning Gleason grades. Mun et al 13 recently published the YAAGGS deep learning system on a large data set from two hospitals. For Gleason grade group prediction, their technique had a 77.5% accuracy and a kappa of 0.65.…”
Section: Discussionmentioning
confidence: 99%
“…The model and designated pathologist had an AUC of 0.960 for identifying cancer and a mean pairwise kappa of 0.62 for assigning Gleason grades. Mun et al 13 recently published the YAAGGS deep learning system on a large data set from two hospitals. For Gleason grade group prediction, their technique had a 77.5% accuracy and a kappa of 0.65.…”
Section: Discussionmentioning
confidence: 99%
“…Manual reading of core needle biopsy slides by pathologists is the gold standard in the prostate cancer diagnosis in the clinic. However, it requires the analysis of around 12 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) biopsy cores, including hundreds of glands. Especially for low-grade and low-volume prostate cancer (GS 3+3 and 3+4), identifying the few malignant glands among vastly benign glands is a tedious and challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the assistance of machine learning systems significantly improves the diagnosis and grading of prostate cancer by pathologists [4,5]. A few studies developed successful machine learning systems for prostate cancer diagnosis and grading to assist pathologists [6][7][8][9][10][11][12][13][14]. They covered a broad spectrum of grade groups.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in our proposed system, we extract overlapping patches to maintain the connectivity of the renal tissue and avoid any loss of contextual and spatial information. In [ 23 ], the authors implemented the CLAM model for prostate cancer grading and compared multiclass MIL with CLAM and their proposed system. The multiclass MIL outperformed CLAM in terms of classification accuracy.…”
Section: Introductionmentioning
confidence: 99%